Reciprocal orthoses in rehabilitation system in children with progressing neuromuscular pathology - Chernyshova, Irina (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Children with progressive neuromuscular disorders need complex rehabilitation the main element of which is verticalization of patients by means of orthosis systems after the conservative and/or surgical preparation. One of the ergonomic devices for passive, passive-active walking are reciprocal orthoses design features of which provide a back-and-forth (reciprocal) walking in patients. Objective: To determine the feasibility and efficacy of reciprocal orthosis in the rehabilitation of children with progressive neuromuscular disorders. Methods: The results of the clinical, radiological and physiological studies of 41 children with a lack of gait due to progressive neuromuscular disorders in age between 2 and 12 years after 1.3 and 5 years. The main group consisted of children who have used for passive-active walk reciprocal orthosis — 23 with spinal amyotrophy, 2 with progressive muscular dystrophy and with 2 myopathic syndrome. The control group consisted of patients who are in the process of motor rehabilitation have used of locking orthosis systems — 10 children with spinal amyotrophy, and 4 with progressive muscular dystrophy. Results: The training walking with reciprocal orthosis allowed to restore the function of independent movement in it in 9 (33 %) children, to increase the overall motor activity (Test Hammersmith), to increase the bioelectrical activity of the lower limbs muscles, to reduce the deficit in living lung capacity, to maintain the function of the cardiovascular and pulmonary systems. Conclusion: Using of the orthosis with reciprocal mechanism is significantly more effective in the rehabilitation of children with progressive neuromuscular disorders comparing to conventional interlocking orthosis systems.